2019
DOI: 10.1108/mf-04-2018-0140
|View full text |Cite
|
Sign up to set email alerts
|

Return reversal effect in Shanghai A share market

Abstract: Purpose The existing literature about return reversal effect in Chinese stock markets is inconclusive and controversial. Therefore, the purpose of this paper is to investigate the presence of return reversal effect in the Shanghai A stock market. Design/methodology/approach The authors used the late-stage contrarian strategy of Malin and Bornholt (2013) for the period March 2011‒March 2016. Findings The results show that there is a long-term return reversal effect in the Shanghai A stock market for the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…They support the rational behaviour of investor and also suggested that longmaturity options investors tend to "overreact" to changes in the implied volatility of shortmaturity options. Using the late-stage contrarian strategy of Malin and Bornholt (2013) and Reddy et al (2019) in their study, find a long-term return reversal effect and a significant short-term momentum effect in the Shanghai A-stock market stocks. Further, they have documented portfolios having small size and lower book to market values explain a large portion of return reversal effect.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…They support the rational behaviour of investor and also suggested that longmaturity options investors tend to "overreact" to changes in the implied volatility of shortmaturity options. Using the late-stage contrarian strategy of Malin and Bornholt (2013) and Reddy et al (2019) in their study, find a long-term return reversal effect and a significant short-term momentum effect in the Shanghai A-stock market stocks. Further, they have documented portfolios having small size and lower book to market values explain a large portion of return reversal effect.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Shumway and Wu (2006) document disposition effect as a driving factor of momentum effect in the Chinese stock market. Reddy et al (2019) examined return reversal effect in the Shanghai A-share market. With the application of late-stage contrarian strategy of Malin and Bornholt (2013) for the period March 2011-2016, they demonstrate the presence of long-term reversal effect in the Shanghai A-share market.…”
Section: Introductionmentioning
confidence: 99%
“…Vo and Troung (2017) studied winner and loser portfolios in the Vietnamese market and evidenced significant momentum. Reddy et al (2019) examined the reversal phenomenon in the Shanghai A stock market and evidenced short-term continuations and long-term reversals.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, without testing the robustness for the emerging markets, it is hard to agree with the above notion's universality. The emerging markets have less developed stock markets which have low liquidity and less industrialisation and higher transaction costs with high growth potential and more open for economic liberalisation (Bekaert, Harvey and Lundblad, 2007).Also, differential behaviours of stakeholders in the emerging markets require diverse measures to deal with market information (Reddy, Qamar and Rao, 2019).The motivation of the study lies in the seminal work of contrarian investing (Lakonishok, Shleifer and Vishny, 1994). In this paper, the authors argued "value stocks would be fundamentally riskier than glamour stocks if, firstly, they underperformed glamour stocks in some states of the world, and secondly, these are on an average in "bad" states, in which the marginal utility of wealth is high, making value stocks unattractive to risk-averse investors."…”
Section: Introductionmentioning
confidence: 99%